Osteofibrous dysplasia: A rare case in 3-day-old female - Anna Castaldo, MD; Angela Siervo, MD; Dolores Ferrara, MD; Anna Marcella Giugliano, MD; Maria Elena Errico, MD; Massimo Zeccolini, MD; Francesco Esposito, MD (Radiology Case Reports, 2022)
Osteofibrous dysplasia (OFD) is a nonneoplastic tumor-like lesion, made up of fibrous matrix with immature bone tissue surrounded by osteoblasts, occurring usually in the cortex of tibial diaphysis. OFD is usually seen in the first decade of life and, according to literature, it is rarely seen in the newborn period. Diagnosis of congenital OFD in the newborn is challenging because it is uncommon in this age group and can be confused with other bone benign or malignant lesions. Imaging plays an important role in diagnosis, although histological confirmation is often required. Our report presents a rare case of pathologically confirmed congenital OFD in 3-day-old female which presented with a swelling of her right leg. We will focus on imaging findings of OFD and main differential diagnosis of this lesion in neonatal age.